2018
DOI: 10.3892/ol.2018.8682
|View full text |Cite
|
Sign up to set email alerts
|

Classical Hodgkin lymphoma arising from heterotopic Warthin's tumor in the cervical lymph node: A case report

Abstract: Abstract. Heterotopic Warthin's tumor (WT) arising from the cervical lymph nodes is uncommon and WT presenting concomitantly with classical Hodgkin's lymphoma has only been previously reported three times in English literature. The current study presents an unusual case of classical Hodgkin lymphoma (CHL) involving the heterotopic WT in a 59-year-old male. Histopathologic examination revealied a WT with extensive expansion of mixed-cellularity CHL in a lymph node in the right of the neck. Clinical staging was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Primary parotid gland lymphomas are rare and, as described in the literature, predominate in elderly patients with a mean age of 65 years [6,7], in the male sex [5][6][7], and mainly affect the parotid gland [6,7], very similar to the case of our patient.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Primary parotid gland lymphomas are rare and, as described in the literature, predominate in elderly patients with a mean age of 65 years [6,7], in the male sex [5][6][7], and mainly affect the parotid gland [6,7], very similar to the case of our patient.…”
Section: Discussionsupporting
confidence: 86%
“…However, transformation to lymphomas, as in our case, is very rare [ 7 , 9 ], with no more than 30 cases reported in the literature [ 6 , 7 ]. The risk factors for malignancy are not entirely clear; exposure to radiotherapy has been proposed [ 10 ] in our case, there was no such history; however, in the cases reported by Ozkök G et al, Li Jun et al, Wang CS et al and some other authors, they report a history of heavy smoking [ 6 , 7 , 9 ] which could be a predisposing factor for transformation to lymphoma as in our case. Some diseases, such as Sjogren's syndrome or Mikulicz's disease, are also risk factors for malignant transformation [ 1 , 3 , 10 ].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Giardini et al reported bilateral parotid gland Warthin tumor involvement with follicular lymphoma [12]. Reiner et al reported a case of large cell lymphoma in association with Warthin tumor, in a patient having preexisting Sjogren syndrome [19]. Generally, a bone marrow biopsy for these patients may show involvement by small clonal B cell population.…”
Section: Discussionmentioning
confidence: 99%